2019
DOI: 10.1111/hsc.12753
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, emotional problems, and behavioural problems of adolescents in China: Roles of mindfulness and life skills

Abstract: While emotional and behaviorial problems increase risks to youth development, resilience helps youth adapt and overcome adversity. Research has discussed factors related to youth resilience, emotional problems, and behaviorial problems; however, existing literature excludes non‐western sociocultural contexts and has not explored the potential relations among mindfulness and life skills. This study examines the effects of mindfulness and life skills on resilience, emotional problems, and behaviorial problems of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
1
13
1
Order By: Relevance
“…In one study, the mindfulness intervention group reported significant decreases on rumination, intrusive thoughts, and emotional arousal [ 78 ]. In another mindfulness-based intervention that incorporated concepts from life skill training, mindfulness was associated with reductions in adolescent emotional and behavioral problems, while life skills were associated with greater resilience [ 39 , 55 ]. Given our findings, interventions such as these can be used to improve the QoL of students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, the mindfulness intervention group reported significant decreases on rumination, intrusive thoughts, and emotional arousal [ 78 ]. In another mindfulness-based intervention that incorporated concepts from life skill training, mindfulness was associated with reductions in adolescent emotional and behavioral problems, while life skills were associated with greater resilience [ 39 , 55 ]. Given our findings, interventions such as these can be used to improve the QoL of students.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found positive relationships between mindfulness and resilience [ 15 , 38 , 39 , 40 ]. Meanwhile, resilience and life satisfaction were shown to have a significant positive relationship in a sample of 1400 Chinese college students [ 41 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The total sum of item scores was used as our measure of life skills and ranged from 10 to 50. In addition to the preceding measures, we also included participant age and gender as the covariates for resilience (Huang et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The empirical literature has provided ample evidence of supporting theoretical framework of the resilience theory that mindfulness and life skills improve individual mental awareness and behavioral skills that lead to increased level of resilience (e.g., Huppert and Johnson, 2010;Jha et al, 2017;Kummabutr et al, 2017;Botvin LifeSkills Training, 2018;Huang et al, 2019) and that high level of resilience is associated with low level of EBPs among children and adolescents (e.g., Ziaian et al, 2012;Arslan, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the psychological measurement characteristics of the RS-14 were tested in 60 adolescents from a Beijing school for students with poor behaviour. This indicated that enhanced resilience is related to life skills, while ameliorating behavioural and emotional problems is connected to “mindfulness” [ 36 ]. Chung et al using data from 1,816 Hong Kong Chinese adolescents, concluded that it is highly important to formulate intervention measures to enhance the resilience of teenagers and promote their positive mental health [ 37 ].…”
Section: Introductionmentioning
confidence: 99%